2012
DOI: 10.1029/2012je004139
|View full text |Cite
|
Sign up to set email alerts
|

Ion densities and composition of Titan's upper atmosphere derived from the Cassini Ion Neutral Mass Spectrometer: Analysis methods and comparison of measured ion densities to photochemical model simulations

Abstract: .[1] The Cassini Ion Neutral Mass Spectrometer (INMS) has measured both neutral and ion species in Titan's upper atmosphere and ionosphere and the Enceladus plumes. Ion densities derived from INMS measurements are essential data for constraining photochemical models of Titan's ionosphere. The objective of this paper is to present an optimized method for converting raw data measured by INMS to ion densities. To do this, we conduct a detailed analysis of ground and in-flight calibration to constrain the instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 71 publications
(198 reference statements)
3
79
0
Order By: Relevance
“…Thus, in addition to very large observational uncertainties, 40 Ar is most likely not truly inert. Mandt et al [2012] suggested that the major stable isotopes of 14 N/ 15 significantly improved counting statistics, which is evident in Figure 2d. As can be seen in Figure 2d and in Table 4, the models using a lower methane homopause, models B and B (HE), calculate isotope ratios outside the INMS uncertainties.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Thus, in addition to very large observational uncertainties, 40 Ar is most likely not truly inert. Mandt et al [2012] suggested that the major stable isotopes of 14 N/ 15 significantly improved counting statistics, which is evident in Figure 2d. As can be seen in Figure 2d and in Table 4, the models using a lower methane homopause, models B and B (HE), calculate isotope ratios outside the INMS uncertainties.…”
Section: Discussionmentioning
confidence: 63%
“…As seen in this figure and as quantified in Table 4, model A represents a superior fit to these isotopic ratios. Moreover, as noted in Mandt et al [2012], these isotope ratios possess lower counting statistical uncertainties and may function as a more reliable diagnostic for eddy diffusion than 40 Ar.…”
Section: Eddy Diffusion: Homopausementioning
confidence: 99%
See 2 more Smart Citations
“…The ionosphere, peaking typically at altitudes of 1000-1100 km, is composed of hydrocarbon ions, nitrile ions, and other complex organic molecular ions, including ones being negatively charged, and is now known to be an important source region for Titanʼs organic aerosols (e.g., Coates et al 2007;Vuitton et al 2007;Waite et al 2007;Crary et al 2009;Wahlund et al 2009;Mandt et al 2012;Lavvas et al 2013;Wellbrock et al 2013;Shebanits et al 2013). The electron number density profile displays the basic variations anticipated from Chapman theory.…”
Section: Briefly On Titan's Ionosphere and Its Ionization Balancementioning
confidence: 99%